The changes in classical and nonlinear parameters after a maximal bout to elicit fatigue in competitive swimming - Barbosa, Tiago (2018)
The aim was to assess the effect of fatigue on linear and nonlinear parameters in swimming. Twenty-four fitness-oriented swimmers performed a maximal bout of 100m at front-crawl to elicit fatigue. Before (pre-) and immediately after (post-test) the bout, participants swam an all- out 25m to derive the speed fluctuation (dv), approximate entropy (ApEn) and fractal dimension (FD) from the speed-time series collected by a speedo-meter. Swim speed was 10.85% slower in the post-test than in the pre-test (p<0.001, η2=0.72). There was an effect of the fatigue on the dv with a moderate effect size. The dv increased shifting the 95CI band from 0.116-0.134 to 0.140- 0.161. The ApEn showed non-significant variations between the pre- and post-test having the 95CI of pre- and post-test overlapped (pre: 0.659-0.700; post: 0.641-0.682). The FD showed as well a significant variation (the 95CI moved from 1.954-1.965 to 1.933-1.951). It can be concluded that in swimming there are changes in classical and nonlinear parameters under fatigue.